Die Kultur tropischer Fruchtbäume in Südafrika - Wiese, Bernd (ERDKUNDE, 1971)
In the agricultural areas on the east side of South Africa, the tropical fruit trees found in the Transvaal, Natal and Cape Province include papaya, guava, mango, avocado and lychee (Fig. 1, Tab. 2). Their area of origin is in the tropical areas of, respectively, the New World (papaya, avocado, guava) and the Old World (mango), and in the subtropical areas of East Asia (lychee). Since the second half of the 19th century these varieties of fruit tress have spread from Cape Province (in the case of guava and avocado) and from Natal (papaya, mango and lychee) under the cultivation of white farmers and Indian market gardeners. Particular ecological conditions and the existence of selectively bred strains allows cultivation of these tropical trees in subtropical South Africa. The freedom from frost of the coastal lowland of Natal and of parts of the Trans vaal low veld; and the mean annual temperatures of 18-21 °C in these lowlands, has encouraged the cultivation of papaya, mango and lychee (Fig. 2). The mist zone along the Drakensberg Hills between 900 m and 1,300 m altitude offers the best conditions for the avocado (Fig. 2). The moderate temperatures of the Cape winter rain area and the medium altitude of the Drakensberg Hills (800-1,000 m) supports guava cultivation. The joint influence of ecological factors and economic space has located the main areas of cultivation in the east and north of the Transvaal (1967: 90%of total production); in the coastal zone of Natal around Durban-Pinetown-Inanda-Port Shepstone; and in Cape Province near East London and Capetown (Fig. 1). The population concentrations of the Witwatersrand-Pretoria conurbation and the other South African cities (Fig. 3) provide the main markets; avocadoes are also exported (Fig. 4). The Citrus and Subtropical Fruit Research Institute in Nelspruit, eastern Transvaal, is the most important research institution for this branch of production. In the agricultural areas on the east side of South Africa, the tropical fruit trees found in the Transvaal, Natal and Cape Province include papaya, guava, mango, avocado and lychee (Fig. 1, Tab. 2). Their area of origin is in the tropical areas of, respectively, the New World (papaya, avocado, guava) and the Old World (mango), and in the subtropical areas of East Asia (lychee). Since the second half of the 19th century these varieties of fruit tress have spread from Cape Province (in the case of guava and avocado) and from Natal (papaya, mango and lychee) under the cultivation of white farmers and Indian market gardeners. Particular ecological conditions and the existence of selectively bred strains allows cultivation of these tropical trees in subtropical South Africa. The freedom from frost of the coastal lowland of Natal and of parts of the Trans vaal low veld; and the mean annual temperatures of 18-21 °C in these lowlands, has encouraged the cultivation of papaya, mango and lychee (Fig. 2). The mist zone along the Drakensberg Hills between 900 m and 1,300 m altitude offers the best conditions for the avocado (Fig. 2). The moderate temperatures of the Cape winter rain area and the medium altitude of the Drakensberg Hills (800-1,000 m) supports guava cultivation. The joint influence of ecological factors and economic space has located the main areas of cultivation in the east and north of the Transvaal (1967: 90%of total production); in the coastal zone of Natal around Durban-Pinetown-Inanda-Port Shepstone; and in Cape Province near East London and Capetown (Fig. 1). The population concentrations of the Witwatersrand-Pretoria conurbation and the other South African cities (Fig. 3) provide the main markets; avocadoes are also exported (Fig. 4). The Citrus and Subtropical Fruit Research Institute in Nelspruit, eastern Transvaal, is the most important research institution for this branch of production.